(untitled) (Revista Internacional de Formação de Professores, 2019)
The present study aims to reflect on the concept of interdisciplinarity and teacher training in a historical perspective. Among the authors analyzed, IvaniFazenda highlights a link of five principles that subsidize an interdisciplinary teaching practice:humility; coherence; wait; respect and detachment. We intend to understand some emerging paradigms of interdisciplinary knowledge, of formative actions that link theory and practice in undergraduate courses.The analysis of this study presents some debates related to the interdisciplinary knowledge and the fragmented disciplinary theory, aiming to contribute to a reflection about the formation of the teacher.